2022
DOI: 10.1039/d2cp00889k
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing dark state kinetics and single molecule fluorescence of FusionRed and FusionRed-MQ at low irradiances

Abstract: The presence of dark states causes fluorescence intermittency of single molecules due to transitions between “on” and “off” states. Genetically encodable markers such as fluorescent proteins (FPs) exhibit dark states...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…The structure and dynamics of the chromophore environment are obviously critical for controlling ultrafast dynamics which lead to nonradiative decay of the excited state, thus limiting the fluorescence quantum yield. In most bright red FPs (RFPs), the chromophore occupies a cis -phenolate conformation in the ground state with the phenolate exhibiting a single-bond character and the negative charge localized on the O atom of the phenol moiety. , Many recent studies have identified the rotation of the chromophore’s P-bond as a primary pathway of ultrafast nonradiative decay. , For example, in mCherry-like FPs, Drobhizev and co-workers examined the roles of several side chains near the MYG chromophore in restricting access to twisted intramolecular charge transfer (TICT) states through phenolate-bond (P-Bond) rotation . The presence of these TICT states permits ultrafast nonradiative decay through a conical intersection seam on the excited state surface.…”
Section: Introductionmentioning
confidence: 99%
“…The structure and dynamics of the chromophore environment are obviously critical for controlling ultrafast dynamics which lead to nonradiative decay of the excited state, thus limiting the fluorescence quantum yield. In most bright red FPs (RFPs), the chromophore occupies a cis -phenolate conformation in the ground state with the phenolate exhibiting a single-bond character and the negative charge localized on the O atom of the phenol moiety. , Many recent studies have identified the rotation of the chromophore’s P-bond as a primary pathway of ultrafast nonradiative decay. , For example, in mCherry-like FPs, Drobhizev and co-workers examined the roles of several side chains near the MYG chromophore in restricting access to twisted intramolecular charge transfer (TICT) states through phenolate-bond (P-Bond) rotation . The presence of these TICT states permits ultrafast nonradiative decay through a conical intersection seam on the excited state surface.…”
Section: Introductionmentioning
confidence: 99%
“…The “dark state” in fluorescence, which is the unsupported concept that there is a time lag between the moment of excitation and the beginning of emission is believed to be very short, even shorter than the emission, and has been called “nonexistent”,with evidence that “remain scarce” [ 65 , 68 ]. All of these times are orders of magnitude shorter that the dwell time of the odorant ligands on the OR which are on a millisecond timescale [ 69 ].The combination of a brief, if even existent “dark state”, along with ns and ps fluorescence lifetimes indicates the release of the multiple photons of an odorant set resulting from the decay of high energy states of odorant molecules in ORs following IET would be on a time-scale so brief that they would be experienced as a set by the brain, providing for the time basis for the interpretation of sets of ONs of individual odorant molecules.…”
Section: Luminescence Timingmentioning
confidence: 99%
“…24,25 Many recent studies have identified the rotation of the chromophore's P-bond as a primary pathway of ultrafast non-radiative decay. 9,[26][27][28][29][30][31][32] For example, Drobhizev and co-workers illustrated the roles of several sidechains in proximity of the MYGchromophore in mCherry-like proteins in restricting the ability of the chromophore to access twisted intramolecular charge transfer (TICT) states through phenolate-bond (P-Bond) rotation. 29 The presence of these TICT states permits ultrafast non-radiative decay through a conical intersection seam on the excitedstate surface.…”
Section: Introductionmentioning
confidence: 99%